The voltage-gated potassium channel Kv1.3 regulates peripheral insulin sensitivity - Xu, Jianchao (National Academy of Sciences, 2004)
Kv1.3 is a voltage-gated potassium (K) channel expressed in a number of tissues, including fat and skeletal muscle. Channel inhibition improves experimental autoimmune encephalitis, in part by reducing IL-2 and tumor necrosis factor production by peripheral T lymphocytes. Gene inactivation causes mice (Kv1.3-/-) exposed to a high-fat diet to gain less weight and be less obese than littermate control. Interestingly, although Kv1.3-/- mice on the high-calorie diet gain weight, they remain euglycemic, with low blood insulin levels. This observation prompted us to examine the effect of Kv1.3 gene inactivation and inhibition on peripheral glucose homeostasis and insulin sensitivity. Here we show that Kv1.3 gene deletion and channel inhibition increase peripheral insulin sensitivity in vivo. Baseline and insulin-stimulated glucose uptake are increased in adipose tissue and skeletal muscle of Kv1.3-/- mice. Inhibition of Kv1.3 activity facilitates the translocation of the glucose transporter, GLUT4, to the plasma membrane. It also suppresses c-JUN terminal kinase activity in fat and skeletal muscle and decreases IL-6 and tumor necrosis factor secretion by adipose tissue. We conclude that Kv1.3 inhibition improves insulin sensitivity by increasing the amount of GLUT4 at the plasma membrane. These results pinpoint a pathway through which K channels regulate peripheral glucose homeostasis, and identify Kv1.3 as a pharmacologic target for the treatment of diabetes.